Automated Laboratory Growth Assessment and Maintenance of Azotobacter vinelandii. Issue 3 (3rd March 2021) - Carruthers, Brooke M.; Garcia, Amanda K.; Rivier, Alex; Kacar, Betul
Abstract: Azotobacter vinelandii ( A. vinelandii ) is a commonly used model organism for the study of aerobic respiration, the bacterial production of several industrially relevant compounds, and, perhaps most significantly, the genetics and biochemistry of biological nitrogen fixation. Laboratory growth assessments of A. vinelandii are useful for evaluating the impact of environmental and genetic modifications on physiological properties, including diazotrophy. However, researchers typically rely on manual growth methods that are oftentimes laborious and inefficient. We present a protocol for the automated growth assessment of A. vinelandii on a microplate reader, particularly well‐suited for studies of diazotrophic growth. We discuss common pitfalls and strategies for protocol optimization, and demonstrate the protocol's application toward growth evaluation of strains carrying modifications to nitrogen‐fixation genes. © 2021 The Authors. This article was corrected on 13 January 2022. See the end of the full text for details. Basic Protocol 1 : Preparation of A. vinelandii plate cultures from frozen stock Basic Protocol 2 : Preparation of A . vinelandii liquid precultures Basic Protocol 3 : Automated growth rate experiment of A. vinelandii on a microplate reader